Evolution of genome size in Hawaiian endemic genus Schiedea (Caryophyllaceae) - Kapralov, M; Stift, M; Filatov, D (2009)
Genome sizes may vary by orders of magnitude among relatively closely related species. Gene and genome duplications and movements of transposable elements (TEs) can quickly inflate genome sizes. Whole genome duplications (polyploidization) may be an important source of evolutionary innovation and many fast evolving island genera are known or assumed to be polyploids. Our main aim is to shed light on the question of how genome size evolved within a rapidly diversifying island lineage. We report the estimates of DNA content for 27 species of the Hawaiian endemic plant genus Schiedea and its widespread sister genus Honckenya (Caryophyllaceae: Alsinoideae). Unexpectedly, genomes of Schiedea species appeared to be relatively compact (1.41 to 3.74 pg/cell), compared to Honckenya (8.57 to 10.66 pg/cell). Interestingly, Schiedea species from younger islands tended to have larger genomes than species from older islands, which may be explained by activation of TE transpositions in small populations after colonization events that resulted in the formation of new species on younger islands. To test whether the Schiedea genome has undergone recent polyploidization events we measured divergence between 62 pairs of paralogous genes in S. globosa. The distribution of divergence values was unimodal with a mode of 7%, supporting a single polyploidization event. Dating this event using Schiedea/Honckenya divergence (2%) and Schiedea/Silene divergence (11%) we estimate that it might have occurred in the ancestor of the genera Schiedea and Honckenya, but after the split between the subfamilies Alsinoideae and Silenoideae. © Springer Science + Business Media, LLC 2009.